An application of biometric technology : Iris recognition - Khalifa, Othman Omran; Olanrewaju, Rashidah Funke; Ramli, Mohd Fariz (IIUM Press, 2011)
Human identification has always been an imerest continuously explored by human. 1lIe need for identification comes from the need to detect and to recognize people for security. verification, validation and recognition and many other reasons. One method of identification that attracts among the greatest interest is biometric identification. Biometric identification deals with 11M: identification of various Iraits of our body. Biometric identification relies on the unique traits and p;lllem COIISiSI of voice. face. body, bi1'ihmark, iris, palm-print, finger-prim and many Olhers. AmOilg tho5e. iris recognition generates the greatest anemion in the last 20 )"<,ars due to lhe accuracy and the reliability of the recognilion. Iris recognition is arguably lhe most reliable biomelric identificalion currently available. Iris ties in,ide the the sclera, which is Ihe whiTe part of our eye. Inside the iris lies the pupil. The .haracterisTic of iris is unique for every individual. It also differs between idemical Twins. The characTeristic is even differem belween the left and right eyes. The iri, consists of limitless palleros that made itvery reliable in deteetion and recognition when compare to other biometrics such as thumb-print and facial recognition